Study of target volume effect on efficiency index and paddick comformty index for arteriovenous malformation treatment plans by gamma knife - Arkan Altmimi; Nadiya Younis; Moneer k Faraj (مجلة كلية الطب, 2023)
Background:  Since energy is the product of volume times dosage, volumes are given a weighting that is proportionate to the dose that they have received. This is a result that energy is a measure of how much substance has been absorbed.